Monthly total fog amount at Gobabeb, Namibia - Yue Li; Eugene Marais; Lixin Wang (PANGAEA, 2025)
Based on literature-derived dataset, public-available meteorological observations, and our measurement recordse, we comprehensively compiled a six-decade-long dataset of the monthly and annual fog amount from 1966 to 2023 at Gobabeb, Namibia. Between 1966 and 2002, the daily amount of fog water was recorded at the Gobabeb - Namib Research Institute using a Grunow cylindrical wire mesh screen fog collector (10 cm diameter, 22 cm height, 691.15 cm^2 area) mounted above a rain gauge (Henschel et al., 1998; Henschel and Seely (2008, doi: 10.1016/j.atmosres.2007.11.015)). Afterward, from 1997 to 2002, Standard Fog Collectors (SFCs), consisting of a 1 m^2 vertical polyethylene mesh screen (10,000 cm^2 area) positioned above a 1 m long horizontal funnel, were employed to quantify daily amount of fog water (i.e., event-based fog amount) (Henschel et al., 1998; Henschel and Seely (2008, doi: 10.1016/j.atmosres.2007.11.015)). To maintain data consistency, Henschel et al. (1998) established a linear regression correlation between the daily Grunow-type fog amount and daily SFC-type fog amount (R2 = 0.62), which was utilized to correct and convert Grunow-type fog amount data to SFC units. The corrected monthly Grunow-type fog amount dataset (1966-1996) using the regression line can be obtained from Henschel et al. (1998), and the raw monthly SFC fog amount dataset (1997-2002) is available at Henschel et al. (1998) and Henschel and Seely (2008, doi: 10.1016/j.atmosres.2007.11.015). The raw monthly Grunow-type fog amount dataset (1966-1996) and the mentioned regression line were not shown in Henschel et al. (1998). The event-based SFC-type fog amount dataset from October 2006 to December 2015 was recorded at the Gobabeb - Namib Research Institute. Additionally, we opportunistically recorded event-based fog amount data using the 1 m^2 SFC as a backup between October 2014 and December 2022. Since October 2014, the hourly amount of fog water was recorded by installing a cylindrical Juvik-type louvered screen fog collector (12.5 cm diameter, 40.6 cm height, 1,594.36 cm^2 area) on a Young Model 52202 tipping-bucket rain gauge. The Southern African Science Service Centre for Climate Change and Adaptive Land Management (SASSCAL) provides access to this hourly Juvik-type fog amount data via https://sasscalweathernet.org/w_datarequest_we.php?MIsoCode=NA&MMCS=0#StationAnchor. To ensure data quality from SASSCAL, false fog events (e.g., from rain, drizzle, or strong wind) were eliminated when fog and rain coincided or when the corresponding relative humidity was less than 70%. At the same time, a correlation regression line between event-based SFC-type fog amount and Juvik-type fog amount was quantified during 2020-2021 (R2 = 0.78, p < 0.05). The SFC-type fog amount dataset from 1966 to 2002 and from October 2006 to September 2014 was further corrected and transformed to Juvik units using this regression line. The dataset gap of monthly fog amounts from January 2003 to September 2006 has been supplemented using the interpolation estimation method. To be specific, the monthly average of daily fog amount was calculated using a dataset of monthly fog amount and monthly fog frequency collected from October 2006 to December 2022. The monthly fog frequency from January 2003 to September 2006 was recorded via Henschel (2021, doi: 10.3390/insects12090804). Consequently, missing data on monthly fog amounts from January 2003 to September 2006 were estimated using the observed monthly fog frequency and the estimated monthly average of daily fog amounts. Overall, the influence of the collection device type of fog gauges at the Gobabeb - Namib Research Institute was deemed negligible for long-term fog-water measurements (1966-2022).
In: Li, Y et al. (2025): Monthly and annual total of moisture from 1962 to 2023 at Gobabeb, Namibia [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.981208